A Tour of the Jevons Paradox: How Energy Efficiency Backfires - Blair Fix (Real-World Economics Review, 2024)
According to mainstream thinking, efficiency is a potent tool for conservation — a way to live better while using fewer resources. Unfortunately, this simple narrative is contradicted by overwhelming evidence. Instead of spurring conservation, efficiency seems to stimulate the consumption of more resources. This paper surveys the evidence for efficiency backfire and concludes that efficiency is a general tool for catalyzing technological sprawl.
Keywords: P; P18; Q4; O4; D24; 330; efficiency; energy; Jevons Paradox